Volunteering and the UN sustainable development goals: Finding common ground between national and international volunteering agendas? - Devereux, Peter; Paull, M.; Hawkes, M.; Georgeou, N. (Australian and New Zealand Third Sector Research Inc., 2017)
With volunteering recognised for its invaluable cross-cutting role, this paper seeks common ground between national and international volunteering agendas within the new global context created by the adoption of the United Nations Sustainable Development Goals (SDGs) in January 2016. By highlighting the dearth of research at the intersection between national and international volunteering, and by examining opportunities for collaboration and consolidation, the authors propose that now is the time to bring the separate research agendas together.